Income Analysis of Laundry Services on Pondok Setrika Selatan Bengkulu - Wyke Gualiani P.N; Wagini Wagini; Rina Trisna Yanti (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
The purpose of this study was to analyze income, average income, net income, and BEP Unit and BEP Rupiah laundry business in Bengkulu Selatan ironing lodge in 2016 - 2020. The type of research used in this study is descriptive research with a quantitative approach. Based on the results of the study showed that the net income in 2016 was Rp. 134,325,000, in 2017 Rp.117,528,000, in 2018 Rp. 143,785,000, in 2019 146,603,000, in 2020 Rp. 161,625,000 in the laundry service business of the ironing cottage in South Bengkulu, in 2012-2016 it has reached BEP, it can be seen from the average acceptance and use of laundry services. it can be seen from the BEP rupiah in 2016 Rp. 35,168,000, 2017 Rp. 42,778,000, in 2018Rp. 44,759,000, in 2019 Rp. 51,942,000, in 2020 Rp. 68,902,000 and BEP units in 2016 Rp. 6,476,018,000, in 2017 Rp. 7,367,110,000, in 2018 Rp. 8,612,829,000, Rp. 10,115,028..